KAIRA - The Kilpisjärvi Atmospheric Imaging Receiver Array - McKay, Derek (UiT Norges arktiske universitet, 2018)
Paper I and IV are not available in Munin. Paper I: McKay-Bukowski, D., Vierinen, J., Virtanen, I.I., Fallows, R., Postila, M., Ulich, T., … Turunen, E. (2015) KAIRA: The Kilpisjärvi Atmospheric Imaging Receiver Array — System Overview and First Results. Available in IEEE Transactions on Geoscience and Remote Sensing, 53 (3), 1440–1451. Paper IV: McKay, D., Partamies, N. & Kauristie, K. (2017). Acquisition of optical and riometric keograms for studying auroral electron precipitation. Available in XVIII Geofysiikan Päivät, Geofysiikan seura r.y., 35–38. The Kilpisjärvi Atmospheric Imaging Receiver Array (KAIRA) is a phased-array radio detector located in Arctic Finland, where auroral electron precipitation is common. This unique deployment of a modern radio telescope in an unconventional location has resulted in a novel and powerful instrument capable of carrying out a large variety of remote-sensing, geoscience experiments. This work presents a selection of these and introduces the interferometric imaging riometry method. KAIRA eli Kilpisjärvi Atmospheric Imaging Receiver Array on Pohjois-Suomessa Kilpisjärvellä sijaitseva vaiheistettuihin antenniryhmiin perustuva radiovastaanotin. Alueella revontulet ja niihin liittyvät elektronipresipitaatio on yleistä. KAIRA on moderni radioteleskooppi epätyypillisessä paikassa, mikä on mahdollistanut useiden uusien kaukokartoitus- ja geofysikaalisten kokeiden kehittämisen. Tässä työssä esitellään näitä kokeita sekä niin kutsuttu interferometrisen kuvantavan riometrin menetelmä. Kilpisjärvi Atmospheric Imaging Receiver Array (KAIRA) er en fasestyrt radiomottaker i arktisk Finland, hvor elektronnedbør ofte observeres i forbindelse med nordlys. Denne unike plasseringen av et radioteleskop, på et ukonvensjonelt sted, har resultert i et nytt og kraftig verktøy for fjernmåling, egnet for et stort spenn av eksperimenter innen geovitenskap. I denne avhandlingen presenteres et utvalg av disse eksperimentene og en metode for interferometrisk avbildende riometri introduseres.